Translation Errors In The Process Of Translation - Rahmatillah, Kartini (Journal of English and Education (JEE), 2013)
Translation nowadays is noted as a kind of skill of transferring messages from one language into another language. One cannot translate something without ignoring errors that may happen during the process of translation. These errors are not ignorable since translation deals with how to bring the same message from one language and to make these messages into the same meaning in other language. Form may differ but the message itself cannot be changed. Since this paper is not a result of a research, it is only intended to enlighten translation errors that may occur during the translation process. Some errors are familiar but others may not to some translator due to different cultural background. Regarding to these errors, there are also solution on how to overcome these errors. Though this paper is not a scientific research but still there are information that may be used for translator, especially those who always face these similar errors. In the end, it can be concluded that how expert a translator is, he or she cannot ignore and may face the errors, and it becomes a tricky problem for translators.Keywords: transalation process, errors